KEHARMONISAN RUMAH TANGGA SEBAGAI UPAYA PENCEGAHAN PERCERAIAN PERSPEKTIF ARIS MUNANDAR - Ramadhani, Evania Putri; Irsan, Irsan (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract A harmonious household is indeed the hope of every couple, but the fact is that many households run aground in the middle of the journey and even end it with divorce. The increasing percentage of divorce in Indonesia has recently become a strong indication of the number of couples who fail to realize harmony in the household. Closely related to the strategy taken to realize it. The purpose of this study is to explore household harmony from Aris Munandar's perspective as well as discuss several strategies to realize household harmony and find out its relevance to today's household problems. This qualitative research was conducted with the type of literature research by identifying information on Aris Munandar's study videos on Youtube channels, social media, scientific papers and other sources. The results of this study revealed that a harmonious household according to Aris Munandar is a household based on faith and built on religious guidance, which is able to solve problems appropriately, feels sufficient, full of comfort, and is contained in 3S. There are 6 strategies to realize household harmony. This research also proves that the strategy presented by Aris Munandar is relevant to today's household problems. Keyword: Harmony; Divorce; Prevention Effort; Aris Munandar.